MUNCULNYA PERUSAHAAN PENERBANGAN BARU DI TENGAH KRISIS EKONOMI - Muhammad Nur Nasution (Media Riset Bisnis & Manajemen, 2001)
Even in an economic crisis, Indonesia still establishes at least and new scheduled airlines.  This paper discusses the consequences of this phenomena in Indonesia airline industry it is a new agenda for ERA to maintain the health of competition industry.